2000
DOI: 10.1002/(sici)1099-0992(200001/02)30:1<123::aid-ejsp981>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

The reinstatement of dissonance and psychological discomfort following failed affirmations

Abstract: The research in this article examined the consequences of a failed attempt to reduce dissonance through a self‐affirmation strategy. It was hypothesized that disconfirming participants' affirmations would reinstate psychological discomfort and dissonance motivation. In Experiment 1, high‐dissonance participants who affirmed on a self‐relevant value scale and received disconforming feedback about their affirmations expressed greater psychological discomfort (Elliot & Devine, 1994) than either affirmation‐only p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 37 publications
5
39
1
Order By: Relevance
“…This finding is consistent with the research of Galinsky, Stone, and Cooper (2000) who found that the tension associated with cognitive dissonance was only seemingly reduced by a global self-affirmation. That tension state (and dissonance) was easily reintroduced if one's global affirmation strategy was subsequently challenged.…”
Section: Resultssupporting
confidence: 92%
“…This finding is consistent with the research of Galinsky, Stone, and Cooper (2000) who found that the tension associated with cognitive dissonance was only seemingly reduced by a global self-affirmation. That tension state (and dissonance) was easily reintroduced if one's global affirmation strategy was subsequently challenged.…”
Section: Resultssupporting
confidence: 92%
“…This result is consistent with other value-based self-affirmation studies (Galinsky et al, 2000;Schmeichel & Martens, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…The recent history of research on stereotyping has shown stereotypes to be fairly ubiquitous, triggered in what has been described as part and parcel of the perception process. One efficient form of control would be to stop these 3 The only experimental data that begins to address the issue of whether tension states linger at the implicit level following self affirmation (where people consciously report an apparent resolution to the tension) comes from Galinsky, Stone and Cooper (2000). Their research focused on the tension associated with cognitive dissonance and found that despite affirmation reducing dissonance, that tension state (and dissonance) was easily re-introduced.…”
Section: Resultsmentioning
confidence: 99%